Lexical Bundles in Students' Argumentative Essays: A Study of Learner Corpus - Ikmi Nur Oktavianti; Japen Sarage (Indonesian Journal of EFL and Linguistics, 2021)
This study investigates the structures of 3- to 5-word bundles used by EFL learners at the university level in writing argumentative essays. This qualitative corpus-based study focuses on answering the structural category and frequency of lexical bundles in students’ essays. The data of this study are sentences containing lexical bundles in the students’ essays, and the data were collected from students' essays compiled as a learner corpus. The lexical bundles were identified from the corpus with the assistance of a corpus tool, LancsBox, using the n-gram feature. This study used ten occurrences as the cutoff frequency and Gries’ DP as the dispersion threshold to identify the lexical bundles. The bundles were then classified into structural taxonomies, and the frequency of use of the lexical bundles was also investigated to complete the analysis. Academic Formulas List comprising bundles commonly used in the academic context was used to validate the bundles. The results show enormous structures of NP-based, VP-based, PP-based, and others identified in the learner corpus with NP-based bundles as the most frequent bundles and ‘the use of’ as the most frequent individual bundle. However, the variants of the bundles in the learner corpus are still dominated by fixed frames. In addition, apart from the shared bundles between the corpus and Academic Formulas List, there are some discrepancies related to the registers. It indicates that writing courses and writing materials should provide learners with more variants of lexical bundles and the appropriate context of use.